Using a mixture of cottonseed hulls and cottonseed meal to replace alfalfa hay in diets for stressed feeder calves - T.B. Farran; R.D. Hunter; Sean P. Montgomery; J.J. Sindt; Dale A. Blasi; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2001)
One 28-day receiving experiment was conducted using 625 exotic x British cross heifers to evaluate growth performance and morbidity on receiving diets that contained either alfalfa hay or a pellet composed of 65% cottonseed hulls and 35% cottonseed meal as the roughage source. Heifers fed the cotton byproduct pellet consumed more feed (P0.05), and the percentages of heifers diagnosed, treated, or retreated for respiratory disease were similar.
Keywords: Cattlemen' s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Cottonseed hulls; Receiving cattle; Health